2018
DOI: 10.5812/jjm.62379
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori in Southern Part of Iran

Abstract: Background: There are clear variations between and within countries regarding the prevalence of Helicobacter pylori. In addition, there are no estimations of its prevalence in the general population in the south of Iran. Objectives: We aimed to evaluate the prevalence of H. pylori in the rural population of Kavar, a southern city of Iran. Methods: A random sample of 500 individuals were selected from the Kavar cohort study. Serum total IgG against H. pylori was checked. The serum positive patients recalled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
3
2
Order By: Relevance
“…( 14) It also maybe because of very low and stable population exposure to H. pylori in this region. (20) This nding is inconsistent with previous reports from developed countries, which showed a decreasing trend for the incidence of GC. (22,23)However, this could be considered as a starting point for the signi cant decrease in the incidence of GC in this region.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…( 14) It also maybe because of very low and stable population exposure to H. pylori in this region. (20) This nding is inconsistent with previous reports from developed countries, which showed a decreasing trend for the incidence of GC. (22,23)However, this could be considered as a starting point for the signi cant decrease in the incidence of GC in this region.…”
Section: Discussioncontrasting
confidence: 91%
“…(17,18) It may be due to higher socio-development, lower prevalence of Helicobacter pylori, and higher healthcare coverage in this region compared with other regions. (19)(20)(21) Our results showed that the overall trend of ASRs of GC has been stable from 2009 to 2015. According to the joinpoint regression, the last observed trends had been started in 2009.…”
Section: Discussionmentioning
confidence: 71%
“…According to the results of this study, the seropositivity against H. pylori using ELISA kit for IgG, IgM, and IgA antibodies was 53.1%, 1.1%, and 0.2%, respectively. Some researchers reported 57.6% and 60.5% rates for IgG (35,36) that are in agreement with our results, while others reported 72.9%, 60%, and 21.2% rates which are inconsistent with our findings (29,37,38). The results of IgA were consistent with an earlier study which was 2.64% (39).…”
Section: Discussioncontrasting
confidence: 51%
“…Furthermore, our results nearly similar in the prevalence of infections age groups whereas by contrast the results are disagree in the rates of infections in males and females some Iraqi studies, where in our results the rate of males higher than females, but in study of Albadri [25] and the study of Majeed & Khoshnaw [26] the rates of infections were higher in females than males. In the final analysis, these differences among the rates of infections in males and females may as a result of the effect of socioeconomic situations, the geographical area, the level of education and the life style according to many research in the developing and developed countries, as exemplified by the research of Ozaydin et al [27], Eshraghian [28], Alsulaimany et al [29], Balas et al [30], Niknam et al [31], (Khoder et al [32], Alfaray et al [33]. In the current study, the small size and shortage of the data with lack of other socioeconomic factors may affect the accuracy and outcome of the findings.…”
Section: Discussionmentioning
confidence: 99%